Algoritmo Para Resolver Operaciones Combinadas Con Números Reales - Cerda, Leonidas; Dávalos, Martha; Morocho, Janneth (European Scientific Journal, ESJ, 2018)
In arithmetic with real numbers, it is essential that students hierarchize the operations to reduce arithmetic polynomials. The domain of these operations forms the basis for understanding other mathematical structures that are studied throughout the student’s life. Building the practice of this knowledge will facilitate future learning in the area of mathematics. In this research it was proved that the use of an appropriate algorithm to realize operations with real numbers positively affects the learning of the students who enter the Higher Polytechnic School of Chimborazo, Faculty of Natural Resources, Agronomy Career.